Системний аналіз екологічно небезпечних процесів різної природи - Selin, Yu. М. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2018)
The current status of researches in the area of preservation of the environment under the negative influence of ecologically dangerous processes of different nature is reviewed. The interaction and interdependence of processes of the same and different types are displayed. Classification of these processes, which is built on their genesis after the degrees of influence on them, and also means for prevention or minimization of possible loses for the ecological environment due to their destructive action are offered.